Ferdinand Tönnies' appraisal of Karl Marx: Debts and distance. (February 2013) - Bond, Niall
Ferdinand Tönnies determined the future course of German sociology with his Marxist analysis of capitalist society in Gemeinschaft und Gesellschaft . He published a biographical introduction to Marx in 1920 and produced discourses influenced by Marxism throughout his life. Notwithstanding his admiration for Marx and his interest in remedying inequities in distribution, he differs with Marx inter alia over the contribution of production factors to wealth, the qualification of the proletariat to rule and the place for ethics in analysis. Tönnies, whose cautious temperament kept him clear of revolutionary movements in Germany and abroad, supported Ethical Culture and the cooperative movement. The denunciation of commercialism by Marx and Tönnies and the teleologies of Tönnies and Marx are compared and contrasted. Tönnies' pessimistic narrative of rationalization and alienation, based upon nineteenth-century assumptions related to the human sciences' vocation to project societal developments, may today appear more founded than Marxist conjectures as to a socialist future.